A meta-analysis exploring the role of PET and PET-CT in the management of potentially resectable colorectal cancer liver metastases. Issue 8 (August 2019) - Daza, Julian F.; Solis, Natalie M.; Parpia, Sameer; Gallinger, Steven; Moulton, Carol-Anne; Belley-Cote, Emilie P.; Levine, Mark N.; Serrano, Pablo E.
Abstract: Background: Positron emission tomography (PET), alone or combined with computed tomography (CT), potentially enhances detection of occult metastatic colorectal cancer. Methods: We compared the impact of PET/PET-CT with conventional imaging, versus conventional imaging alone, in patients with potentially resectable colorectal cancer liver metastases. MEDLINE, EMBASE, and CENTRAL were searched for studies investigating PET/PET-CT to determine resectability. Outcomes included overall (OS), disease-free survival (DFS), change in surgical management, and futile laparotomy. Evidence quality was assessed using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) framework. A pre-specified protocol was registered in PROSPERO. Results: Of 4034 articles, two randomized trials (n = 554), and 11 non-randomized studies (n = 2251) were included. PET/PET-CT did not improve OS (hazard ratio [HR] 0.94, 95% CI 0.69–1.26, moderate quality) or DFS (HR 1.01, 95% CI 0.82–1.26, moderate quality). In the two trials, PET/PET-CT changed surgical management in 8% of cases (95% CI 5–11%, high quality), and did not significantly reduce futile laparotomies (risk ratio 0.59, 95% CI 0.24–1.47, low quality). Among non-randomized studies, PET/PET-CT changed surgical management in 20% of cases (95% CI 17–22%, very low quality) and reduced futile laparotomies (odds ratio 0.51, 95% CI 0.32–0.81, very low quality). Conclusions: Moderate-quality evidence suggests that preoperative PET/PET-CT does not improve OS or DFS in patients with colorectal cancer liver metastases. These results do not support routine use of PET/PET-CT in patients with potentially resectable disease. The main limitation of this study was the lack of randomized studies. Abstract : Synopsis Moderate-quality evidence from randomized studies suggests that PET and PET-CT do not improve overall or disease-free survival in patients with potentially resectable colorectal cancer liver metastases. Additionally, there is high-quality evidence suggesting that PET/PET-CT changes surgical management in only a select number of cases.